Pemanfaatan Media Sosial Sebagai Media Pembelajaran Pendidikan Agama Islam Bagi Peserta Didik SMP Di Kabupaten Aceh Singkil - Pandapotan Harahap; Fajaruddin Pasaribu; Azwir Aziz; Awaluddin Awaluddin; Hasrian Rudi Setiawan (Pendekar : Jurnal Pendidikan Berkarakter, 2024)
The aim of this research is to determine the effectiveness of implementing social media, especially as a learning medium. The actual facts about the use of social media in the form of the Internet in Indonesia show that technological development is progressing rapidly. Many schools and universities in Indonesia utilize technological advances as a learning medium, including in Islamic religious education. Then, the author applies qualitative methods to determine the impact of the use of social media on learning Islamic religious education for junior high school students in Aceh Singkil Regency both in terms of positive and negative impacts in literature studies. This is also motivated by the recent use of social media It is widely misused by students. Although social media has a positive impact on the social skills of its users, social media can also have a negative impact in real life. This causes changes in children's ability to learn and understand Islamic religious education material, both academic abilities and personality.